Immune Responses to Middle East Respiratory Syndrome Coronavirus During the Acute and Convalescent Phases of Human Infection. (27th July 2018) - Shin, Hyoung-Shik; Kim, Yeonjae; Kim, Gayeon; Lee, Ji Yeon; Jeong, Ina; Joh, Joon-Sung; Kim, Hana; Chang, Eunjin; Sim, Soo Yeon; Park, Jun-Sun; Lim, Dong-Gyun
Abstract: Background: An understanding of immune responses against the Middle East respiratory syndrome (MERS) is important for the development of treatments and preventive measures. Here, we investigated the spectrum of immune responses occurring in patients with MERS during the early period of infection. Methods: We obtained peripheral blood samples from 27 hospitalized patients recruited during the epidemic that occurred in 2015 in South Korea. Plasma cytokines/chemokines and antibodies were quantified. Virus-specific T cells were examined by intracellular cytokine staining after stimulation of peripheral blood mononuclear cells with overlapping peptides spanning whole virus structural proteins. Results: At the acute phase of infection, elevated levels of plasma proinflammatory cytokines/chemokines were detected in proportion to the severity of the disease. Distinctively high frequencies of MERS coronavirus–reactive CD8 + T cells were also observed in patients with severe/moderate illness, whereas antibody and CD4 + T-cell responses were minimally detected at this stage. At the convalescent phase, disease severity–dependent antibody responses emerged and antigen-reactive cells were identified in both T-cell subsets. These T cells belonged to the T-helper 1 or type 1 cytotoxic T cell subtypes. While CD8 + T cells responded preferentially to the viral S protein compared with E/M/N proteins, especially at the acute stage, slightly more CD4 + T cells recognized E/M/N proteins compared with S protein at the convalescent phase. Conclusions: Our findings show an association between the early CD8 + T-cell response and the severity of the infection, and also provide basic information that may help to prepare effective control strategies for MERS in humans. Abstract : Our study examined immune responses to MERS coronavirus at the acute stage of human infection, and shows an association between the early CD8 + T-cell response and the severity of the infection.